THE EFFECT OF DEBT TO EQUITY RATIO AND GOOD CORPORATE GOVERNANCE AGAINST FIRM VALUE (STUDY ON MINING SECTOR COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE PERIOD OF 2014-2018) - Situmorang, Gavrila Miranda; Johni Siagian; Melinda Malau (Universitas Kristen Indonesia, 2021)
The study aims to identify the effect of debt to equity ratio and good corporate governance on firm value. Researchers used statitic descriptive, classic assumption test and multiple linier method. This study used data of 10 mining sector companies which has been registered on the Indonesia Stock Exchange (BEI) on period of 2014-2018. The study has the results of the debt to equity ratio, managerial ownership, independent board of commissioners have an effect on firm value. Then institusional ownership, audit committee uninfluence on firm value. Keywords: debt to equity ratio, good corporate governance, firm value